The Analyze About Brief Training of Basic Introductory Speech with Affective Taxonomy Method for English Public Speaking at SMK Giki Surabaya - Pamuji, Wirawan; Anton Hutomo Sugiarto; Putri Ridhotul Uliyah; Mimin Suriadi (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
The Form of Teaching Basic Introductory Public Speaking for Beginners should be adequate Training for Vocational School Students as they could understand not merely intact for the textual material to learn, but also couching for the form The Research applies Descriptive Qualitative Methods in developing Domain of Applicative Affective Domain to perform either language form or ethical way of presentation in English.The application of this couching is about to implement about how students speak in good structure but also how to speak in good manner